Setogenesis and characterization of the new moult substages in the freshwater shrimp Palaemon argentinus (Nobili, 1901) (Caridea: Palaemonidae) - Foguesatto,Kamila (2019)
Abstract The moult cycle of crustaceans is continuous and during different stages of this cycle, physiological, biochemical and morphological changes occur. Therefore, understanding the different stages of the moult cycle in the target species becomes critical for a wide range of biological studies. Here we describe the natural cycle changes in the freshwater shrimp Palaemon argentinus and identify two new substages of post-moult, B1 and B2, that are substages occurring before the intermoult, a stage widely used in crustacean studies. Furthermore, we present a more detailed description of stages already known, describing modifications of the structures and its presence or absence in each stage, in conjunction with explanatory pictures. We also indicate the duration for each stage of the cycle, thus expanding our knowledge of the moult cycle and setogenesis for P. argentinus.